Ophthalmic Public Health; the Way Ahead - F Heidary; A Rahimi; R Gharebaghi (Tehran University of Medical Sciences, 2012)
Background: Visual sciences have been progressing quickly in recent decades through globalization phenomenon. An enormous change has taken place in ocular health issues, however, there are various problems facing ophthalmic public health worldwide. In the previous years, the World Health Organization and the International Agency for the Prevention of Blindness in partnership launched the global initiative to eradicate avoidable blindness by the year 2020, VISION 2020 the Right to Sight. It has concentrated on the prevention of blindness disability and recognized a health issue-sight as a human right. In view of challenges ahead of visual sciences, close collaboration between international agencies at the global level to implement new strategies and monitor the progress will be mandatory. In these circumstances non-governmental organizations should not be neglected. World Sight Day 2012 would be a great opportunity to be a focus on importance of visual impairment as an important public health issue and discovering new challenges ahead.